Analisis Penatausahaan Aset Tetap pada Dinas Kesehatan Provinsi Jawa Barat - Ria Lestari; Vita Citra Mulyandini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the process of fixed asset administration at the West Java Provincial Health Office and to identify the underlying issues that have hindered optimal asset management in accordance with Minister of Home Affairs Regulation Number 19 of 2016 on Guidelines for the Management of Regional Property. The research is driven by the importance of proper fixed asset administration in supporting the accuracy of local government financial statements, as well as recurring audit findings from the Audit Board of Indonesia (BPK) indicating irregularities in asset management. Based on an analysis of three main indicators bookkeeping, inventory, and reporting the study finds that the level of compliance in fixed asset administration remains low. Bookkeeping only shows compliance in terms of timeliness, while other aspects are non-compliant. Inventory is identified as the weakest area, with all parameters categorized as “non-compliant.” Reporting performs relatively better, but issues persist regarding data accuracy. The main challenges in asset administration include limited human resources, underutilization of information systems, weak inter-unit coordination, and inadequate documentation of legacy assets. Based on these findings, the study provides several strategic recommendations, including optimizing the use of information systems, conducting regular and comprehensive inventories, strengthening documentation and data validation, enhancing human resource capacity, and improving inter-unit coordination. Implementation of these strategies is expected to improve the quality and accountability of fixed asset administration and support the preparation of transparent and reliable government financial statements.